High rate CO2 valorization to organics via CO mediated silica nanoparticle enhanced fermentation. (1st December 2020) - Jack, Joshua; Lo, Jonathan; Donohue, Bryon; Maness, Pin-Ching; Jason Ren, Zhiyong
Highlights: State-of-the-art hybrid process for CO2 conversion and upgrade to fuels. High CO Faradic efficiency of over 80% on gas diffusion electrode. Excellent organics production rates compared to microbial electrosynthesis. Modified silica nanoparticles increased metabolite titer by 149% High bioethanol production rate of ca. 7 mg/L/h demonstrated in hybrid system. Abstract: Carbon dioxide (CO2 ) valorization to high energy density fuels presents an economically sound approach to directly couple waste mitigation with sustainable energy production, yielding tremendous environmental and societal benefits. Here, a new two-stage hybrid system was developed that pairs highly efficient electrochemical CO2 reduction (CO2 -R) to carbon monoxide (CO) with acetogenic bacteria for the rapid production of green chemicals. This original design seeks to solve issues in mediator production and utilization evident in related studies. A progressive silver-based gas diffusion electrode with anion exchange membrane sustained current densities of 200 mA/cm 2 for over 240 h at a time and produced CO at excellent Faradaic efficiencies of over 80% at a cell voltage ca. 3.2 V. The effluent gas from the CO2 electrolyzer was connected to a bioreactor containing Clostridium ljungdahlii where the blend of CO/CO2 was converted into a mixture of mainly acetate and ethanol. This demonstrates the first time this organism has been tested in a two-stage hybrid CO2 -R system. Competitive acetate and ethanol production rates of 17.87 ± 7.1 and 3.23 ± 1.4 mg/L/h were achieved under autotrophic conditions. In addition, mercapto-modified silica nanoparticles were developed to increase gas mass transfer and resulted in 217% and 224% increases in acetate and ethanol production rates, respectively. This system presents a viable approach to produce sustainable fuels and chemicals in a process that exploits commercially scalable C1 electron carries.